Price structure of cardamom in India - an analysis - NAIDU, TOMY JOSEPH, R (Journal of Spices and Aromatic Crops, 1992)
The seasonal phenomenon in the plice of small cardamom along with the seasonality in related vatiables like sales at auction centres, export and export price are analysed. The interrelationship between market price and these variables is also studied. The analysis shows that the seasonal index of price was the highest in January and the lowest in July, while the seasonal index of market sales was the highest in November and lowest in July. The extent of seasonality was more in sales compared to prices. Compared to export price, sales price showed more marked seasonality. An attempt is made to quahtify the extent of relationship between yearly sales price and variables like production, quantity of sales at auction centres, export and export price by employing multiple regression analysis. The analysis shows that around 97% variation in yearly price can be explained by the two variables namely export and export price. The compound growth rates in production, export and prices during the period are also worked out.